Factors Associated With Cognitive Impairment in Heart Failure With Preserved Ejection Fraction. Issue 1 (January 2022) - Faulkner, Kenneth M.; Dickson, Victoria Vaughan; Fletcher, Jason; Katz, Stuart D.; Chang, Patricia P.; Gottesman, Rebecca F.; Witt, Lucy S.; Shah, Amil M.; D'Eramo Melkus, Gail
Abstract : Background: Cognitive impairment is prevalent in heart failure and is associated with higher mortality rates. The mechanism behind cognitive impairment in heart failure with preserved ejection fraction (HFpEF) has not been established. Objective: The aim of this study was to evaluate associations between abnormal cardiac hemodynamics and cognitive impairment in individuals with HFpEF. Methods: A secondary analysis of Atherosclerosis Risk in Communities (Atherosclerosis Risk in Communities) study data was performed. Participants free of stroke or dementia who completed in-person assessments at visit 5 were included. Neurocognitive test scores among participants with HFpEF, heart failure with reduced ejection fraction (HFrEF), and no heart failure were compared. Sociodemographics, comorbid illnesses, medications, and echocardiographic measures of cardiac function that demonstrated significant ( P < .10) bivariate associations with neurocognitive test scores were included in multivariate models to identify predictors of neurocognitive test scores among those with HFpEF. Multiple imputation by chained equations was used to account for missing values. Results: Scores on tests of attention, language, executive function, and global cognitive function were worse among individuals with HFpEF than those with no heart failure. Neurocognitive test scores were not significantly different among participants with HFpEF and HFrEF. Worse diastolic function was weakly associated with worse performance in memory, attention, and language. Higher cardiac index was associated with worse performance on 1 test of attention. Conclusions: Cognitive impairment is prevalent in HFpEF and affects several cognitive domains. The current study supports the importance of cognitive screening in patients with heart failure. An association between abnormal cardiac hemodynamics and cognitive impairment was observed, but other factors are likely involved.